2020
DOI: 10.2147/ott.s250101
|View full text |Cite|
|
Sign up to set email alerts
|

<p>MicroRNA-939 Directly Targets <em>HDGF</em> to Inhibit the Aggressiveness of Prostate Cancer via Deactivation of the WNT/β-Catenin Pathway</p>

Abstract: MicroRNA-939 (miR-939) has crucial roles in several types of human cancer. However, the expression profile and precise functions of miR-939 in prostate cancer (PCa) are still unclear. This study aimed to determine miR-939 expression in PCa and explore its roles in PCa tumorigenesis. Methods: miR-939 expression was determined in PCa tissues and cell lines using reverse transcription-quantitative polymerase chain reaction. Cell Counting Kit-8, colony formation, and flow cytometric assays were used to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…PCa has a wide diffusion and represents the second major cause of death worldwide because of its aggressive behaviour. 25 MiRNAs have been suggested to be novel diagnostic/therapeutic instruments, as they could play a role as a biomarker in the diagnosis and may also represent possible targets for new therapies. 26,27 In the case of PCa, the interest in miRNA is linked to the fact that prostate-specific antigen shows several limitations, 28,29 as infection, very common in frail patients.…”
Section: Discussionmentioning
confidence: 99%
“…PCa has a wide diffusion and represents the second major cause of death worldwide because of its aggressive behaviour. 25 MiRNAs have been suggested to be novel diagnostic/therapeutic instruments, as they could play a role as a biomarker in the diagnosis and may also represent possible targets for new therapies. 26,27 In the case of PCa, the interest in miRNA is linked to the fact that prostate-specific antigen shows several limitations, 28,29 as infection, very common in frail patients.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has shown that lncRNA is involved in tumorigenesis and cancer progression ( 33 , 34 ). Abnormal miRNA expression is another factor contributing to tumorigenesis by dysregulating target genes related to PC progression ( 14 , 15 ). Meanwhile, several studies have revealed that lncRNA promotes PC growth mainly by regulating genes and pathways supporting cell proliferation ( 1 , 3 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal miRNA expression has also been observed in PC, and complex miRNA regulatory networks and modules have been proposed to regulate PC progression ( 12 , 13 ). Aberrant miRNA expression frequently dysregulates the target genes implicated in carcinogenesis of PC ( 14 , 15 ). Among them, miR-1182 was identified as a tumor suppressor and implicated in the tumorigenesis of different tumor types, such as bladder ( 16 ), ovarian ( 17 ), gastric ( 18 ) and PC ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Prostate cancer (PCa) is among the most common tumour in male. A recent study by Situ et al [ 72 ] provided evidence for the involvement of the microRNA-939 (miR-939) in PCa. Downregulation of miR-939 was found in tumour tissues at advanced tumour stage, in distant lesions, as well as being associated with poor prognosis.…”
Section: Wnt Pathway and Other Cancersmentioning
confidence: 99%